O impacto da criminalidade na demanda turística do nordeste brasileiro - Silva Júnior, Benedito Maciel da (2017)
This paper discusses a possible relationship between a public safety and a motivation of the tourist displacement. For this purpose, it is used in the context of the Northeastern context, one of the main tourism inducing regions in the Brazil. The topic is approached, ranging from the importance of tourism to the economy in the northeast of the Brazil, the level of crime that is a region where a place is located and one of its effects on local demand. In a more comprehensive instance, this study aims to collaborate for a broader discussion of the relationship between public safety and the choice of a tourist destination. Specifically, the paper aims to raise a relevance of taking into account the data related to public safety for tourism planning and to highlight an important one of the quality of the public safety related specifically to the tourism segments in the Brazilian northeast.